La fresque de saint Gilles dans l’église Saint-Nicolas de Civray : image miraculée, image d’un miracle, image miraculeuse ? - Pierre-Antoine Fabre (Images Re-Vues)
Here, we focus on three distinct, sedimented moments in the legend of a founding miracle—the miracle of Gilles as depicted in the abbey church of Civray, in Poitou: the fresco inspired by this legend in the 13th century, the rediscovery of this fresco and its preservation during the « restoration » of the church's medieval décor in the 19th century, and the interpretation of this same fresco in the early 21st century. These three moments raise questions about the resilience of this painted wall panel, which may have been anachronistic even in the original conception of its 13th-century layout.